2019
DOI: 10.1111/cogs.12795
|View full text |Cite
|
Sign up to set email alerts
|

Generating Relations Elicits a Relational Mindset in Children

Abstract: Relational reasoning is a hallmark of human higher cognition and creativity, yet it is notoriously difficult to encourage in abstract tasks, even in adults. Generally, young children initially focus more on objects, but with age become more focused on relations. While prerequisite knowledge and cognitive resource maturation partially explains this pattern, here we propose a new facet important for children's relational reasoning development: a general orientation to relational information, or a relational mind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 43 publications
1
28
0
Order By: Relevance
“…For such distant analogies, the process of generating a D term is likely to be guided by relational comparison to ensure that the resulting C:D relation is sufficiently similar to the A:B relation. Indeed, generating solutions to distant semantic analogies appears to foster a transient "relational set," encouraging a focus on relations in other tasks administered shortly afterward (Andrews & Vann, 2019;Simms & Richland, 2019;Vendetti, Wu, & Holyoak, 2014). More generally, the generation of solutions to distant analogies appears to be closely linked to creative thinking (Green, 2016).…”
Section: Semantic Analogiesmentioning
confidence: 99%
“…For such distant analogies, the process of generating a D term is likely to be guided by relational comparison to ensure that the resulting C:D relation is sufficiently similar to the A:B relation. Indeed, generating solutions to distant semantic analogies appears to foster a transient "relational set," encouraging a focus on relations in other tasks administered shortly afterward (Andrews & Vann, 2019;Simms & Richland, 2019;Vendetti, Wu, & Holyoak, 2014). More generally, the generation of solutions to distant analogies appears to be closely linked to creative thinking (Green, 2016).…”
Section: Semantic Analogiesmentioning
confidence: 99%
“…Vendetti, Wu, and Holyoak (2014) compared the effects of generating solutions to semantically distant four‐term verbal analogies to passively viewing and evaluating completed analogies. Generating solutions to distant analogies selectively fostered the induction of a relational mindset that fostered attention to relational information in a subsequent analogy task using completely different relations (see also Andrews & Vann, 2019; Simms & Richland, 2019). These findings suggest that generating relational information may encourage participants to attend to it.…”
Section: An Analogical Approach To Teaching: Five Principlesmentioning
confidence: 99%
“…It is important to highlight that this modified OMTSvRMTS task has exactly the same structure and choices as the task used in Experiments 2 and 3: The card with the incomplete object match has one object identical on all dimensions with the objects in the sample card while the other match exemplifies the relation same with objects that differ from both of those on the sample card. If adults' relational matching is determined by a general preference for object matches over relational matches (or vice versa) as suggested by previous authors (Simms & Richland, 2019;Vendetti et al, 2014), there should be no difference between performance on this modified OMTSvRMTS task and baseline performance (Experiment 2). In summary, Experiment 4 tests two interrelated hypotheses: (1) Adults' inductive biases are (at least in this case) specified at a more detailed level than a general preference for relations over object features and (2) The inductive biases of adults in our sample are specifically toward shape/color matches.…”
Section: Experiments 4 Methodsmentioning
confidence: 60%
“…Rather, they are meant to illustrate how, using the kind of approach developed with adults above, we can analyze training paradigms that produce success on RMTS and develop testable hypotheses as to whether they may have had their effects through changes to inductive biases alone. Notice also that these hypotheses rely on inductive biases specified at the level of particular bases of matching-in contrast to the content-general bias toward relations suggested by Vendetti et al (2014) and Simms and Richland (2019). We have demonstrated that, at least in the case of adults, the latter interpretation is implausible: No content-general bias would have resulted in a radical difference in percentage of relational matches (56% vs. 93%) between two tasks which are identical but for the dimensions on which the stimuli vary (i.e., OMTSvRMTS in Experiment 2 and 4, respectively).…”
Section: -Possible Effects Of Trainingmentioning
confidence: 87%
See 1 more Smart Citation